Image and Video Processing Applications Using Xilinx System Generator - Yaman, Sertac; Yildirim, Merve; Kamislioglu, Bircan; Erol, Yavuz; Kurum, Hasan (Ieee, 2019)
This paper presents some image and video processing applications by using Xilinx System Generator ( XSG) to implement into Field Programmable Gate Array (FPGA). All algorithms which are gray conversion, inversion, enhancement, erosion and dilation, thresholding, and edge detection are included in this study. These methods are generally applied on an image or a video in the literature. Differently in this study, the algorithms are applied on an image and the video. Besides, the edges of the objects in a video are also detected by utilizing these methods. The design is verified and validated by using XSG at Matlab/Simulink to implement into the FPGA.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Field Programmable Gate Array; image processing; Matlab/Simulink; video processing; Xilinx System Generator